PENGARUH BAHASA DI MEDIA SOSIAL BAGI KALANGAN REMAJA - Octorina, Ira Maulina; Karwinati, Dewi; Aeni, Eli Syarifah (IKIP Siliwangi, 2018)
A language is a communication tool used in everyday life, including in social media, without using Language, communication will not work properly. Social media at this time is a container where its users can shed their expression and desire, especially among teenagers. The language used in social media at this time partly ignore the rules of language is good and true, therefore the learning of Indonesian is good and true in accordance with the rules of language should be learned early on